PELAKSANAAN AZAS PERADILAN CEPAT, MURAH DAN SEDERHANA DALAM KASUS PERCERAIAN DI INDONESIA - Miasiratni Miasiratni; Sri Agustini (Ensiklopedia of Journal, 2025)
This article aims to initiate the implementation of fast, cheap, and simple justice in resolving divorce cases in Indonesia. This principle is a basic principle in the trading system that aims to provide efficient access to justice for the community. This study uses a normative legal method with a qualitative approach, which is based on laws and regulations, court decisions, and related literature studies. The results of the study indicate that although normatively the principle of fast, cheap, and simple justice has been regulated in the Indonesian legal system, its application in divorce cases deals with obstacles. These obstacles include the length of the administrative process, costs that are still felt to be burdensome by some people, and limited facilities and infrastructure in several judicial institutions. Therefore, efforts are needed to improve the system and increase the efficiency of judicial procedures so that as mentioned can truly be realized in practice.Keywords: Fast Justice, Divorce, Low Cost